Reversing extinction trends: new uses of (old) herbarium specimens to accelerate conservation action on threatened species. Issue 2 (13th January 2021) - Albani Rocchetti, Giulia; Armstrong, Chelsey Geralda; Abeli, Thomas; Orsenigo, Simone; Jasper, Caroline; Joly, Simon; Bruneau, Anne; Zytaruk, Maria; Vamosi, Jana C.
Summary: Although often not collected specifically for the purposes of conservation, herbarium specimens offer sufficient information to reconstruct parameters that are needed to designate a species as 'at‐risk' of extinction. While such designations should prompt quick and efficient legal action towards species recovery, such action often lags far behind and is mired in bureaucratic procedure. The increase in online digitization of natural history collections has now led to a surge in the number new studies on the uses of machine learning. These repositories of species occurrences are now equipped with advances that allow for the identification of rare species. The increase in attention devoted to estimating the scope and severity of the threats that lead to the decline of such species will increase our ability to mitigate these threats and reverse the declines, overcoming a current barrier to the recovery of many threatened plant species. Thus far, collected specimens have been used to fill gaps in systematics, range extent, and past genetic diversity. We find that they also offer material with which it is possible to foster species recovery, ecosystem restoration, and de‐extinction, and these elements should be used in conjunction with machine learning and citizen science initiatives to mobilize as large a force as possible to counter current extinction trends.